1976
DOI: 10.1007/bf00295821
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a new type of human fetal hemoglobin carrying a replacement isoleucine ? threonine at position 75 (E 19) of the ? chain

Abstract: A new type of hemoglobin F, in which isoleucine in position 75 (E 19) of the gamma chain is replaced by a threonine residue, has been found in 29 out of 32 homozygotes for beta thalassemia. The amount of this hemoglobin ranges from traces to 40% of the total Hb F. The same gamma75 Thr chain is also present in the Hb F of 40% of normal newborns and premature infants examined, of one 14-week-old fetus and in one out of 3 patients with aplastic anemia and raised levels of Hb F. Our results strongly suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
3
3

Year Published

1979
1979
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(39 citation statements)
references
References 14 publications
1
32
3
3
Order By: Relevance
“…The recent discovery of the Ty-chain by Ricco et al. (3) has added yet another facet to the many ways in which the study of Hb-F has provided data about the genetics ofthis fetal protein. In the Ty-chain, the isoleucyl residue at position 75 of the y-chain is replaced by a threonyl residue.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of the Ty-chain by Ricco et al. (3) has added yet another facet to the many ways in which the study of Hb-F has provided data about the genetics ofthis fetal protein. In the Ty-chain, the isoleucyl residue at position 75 of the y-chain is replaced by a threonyl residue.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recent discovery in a large proportion of normal and thalassemic subjects (8) of a variant -y chain having threonine instead of isoleucine (8,9) METHODS CM-Cellulose Chromatography of Globin Chains. Purified a, f, and y globin chains were obtained by CM-cellulose chromatography (10) of acid/acetone-precipitated total globin chains (10).…”
mentioning
confidence: 99%
“…The globins were submitted to tryptic digestion and to fingerprinting on paper [4] and on thin layer [ll].…”
Section: Methodsmentioning
confidence: 99%
“…A variant of Hb F, Hb F Sardinia (ars$s 75 Ile + Thr) [3] is of unusual high frequency in various populations at birth [4,5]. Very recent results of peptide analysis suggested that the 775 Thr chain is a variant produced by the A7 locus [6,7] and corresponds to a genetic polymorphism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation